Electrical Project Model Using the Local Component Level (TKDN) in Government Building Construction - Mas’ud Dohim; Dyah Erny Herwindiati; Endah Murtiana Sari (Departement of Civil Engineering, Universitas Winaya Mukti, 2026)
The implementation of TKDN level in electrical work is one of the government's strategic policies to enhance national industrial competitiveness, reduce dependence on imported products, and support sustainable infrastructure development. However, the implementation of TKDN in government building construction projects still faces various obstacles, such as the limited availability of TKDN-certified products, low integration between planning and procurement, and the absence of a model capable of explaining the factors that influence the level of TKDN implementation. This study aims to develop an electrical work model using the TKDN level in government building construction by identifying the factors that influence its implementation and analyzing the relationships among these factors with respect to the success of TKDN implementation. The study employed a quantitative approach through the distribution of questionnaires to 210 respondents; the data were then analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to test the relationships among variables and to construct an empirical model. The results produced a model explaining the influence of the unit price of electrical work, electrical material, labor, electrical equipment, and TKDN policy on the level of TKDN implementation, as well as its impact on project performance. The novelty of this study lies in the development of a TKDN implementation model for electrical work that integrates regulatory compliance and supervision, technical, and managerial aspects within a single empirical framework. The resulting model is expected to serve as a basis for decision-making in increasing the use of domestic products in government building projects.